PENGARUH PAID PROMOTE, KUALITAS PRODUK, DAN ONLINE CONSUMER REVIEW TERHADAP MINAT BELI PADA TUMBUH LAB - Tifany, Shindi Alfi; Moeliono, Nadya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Technological development have made a change in consumer behavior from offline to online all over the world especially in Indonesia, one of them because by the growth of online shops. The number of online shops that have sprung up this time has become the center of public attention especially among women because it saving time and they also read various reviews in social media and website rewiew. They have their own belief whether to decide to buy the product or not at all. Considering the existing phenomenon, the research is done to study the effect of paid promote, online consumer review and also product quality. The purpose of this research is to know the effect of paid promote, product quality, and online consumer review on purchase interest in Tumbuh Lab. Tumbuh lab is chosen because it already used paid promote.The sample of this study were 300 responden who were consumer an followers Tumbuh Lab. The research method used a quantitative method and multiple linear regression analyses. The sampling technique used in this study was snowball sampling. The results of the study shows that paid promote, product quality, online consumer review and buying interest are in very good category. The result of simultaneous and simultan significantly influence buying interest and the coefficient of determination shows that paid promote, product quality, and online consumer review significantly influence purchase interest by 32,1% and 67,9% are influenced by other variables outside of this research